Determinants of cost discrepancies in inpatients with acute decompensated heart failure - Arisandi, Jeffri; Lorensia, Amelia; Rahem, Abdul (Universitas Brawijaya, 2025)
BACKGROUND: Acute decompensated heart failure (ADHF) is a prevalent and complex condition that significantly burdens healthcare systems, requiring intensive care and leading to high treatment costs. OBJECTIVES: This study aims to identify factors influencing cost discrepancies in hospitalized ADHF patients. METHODS: This retrospective study was conducted at Universitas Brawijaya Hospital from July to August 2024. Data were collected from 86 ADHF patients who were hospitalized between January 2021 and December 2023. Information regarding the patients' clinical conditions, comorbidities, and medical procedures was extracted from their case histories. Statistical analyses included t-tests and Mann-Whitney tests. RESULTS: In this study of 86 individuals with ADHF, 58.1% were over 65 years old, 31.4% were between 45 and 64 years old, and 10.5% were between 18 and 44 years old. By classification of care, 58.1% were admitted for Class 1 care, 30.2% for Class 2, and 11.6% for Class 3. Our findings indicated that the costs of treatment for patients with moderate and severe diseases were higher as compared to those of mild severity. Patients who had a length of stay over 7 days had higher costs than the ones whose length of stay was 1 to 3 days. Furthermore, Class 2 care was associated with higher costs than Class 3 care. The analysis also revealed that an increase in the number of comorbidities and medical procedures corresponded with higher treatment costs. CONCLUSION: This study identified factors that increase the cost of treatment for patients with ADHF.